2021
DOI: 10.1016/j.fbr.2021.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Evolving challenges and strategies for fungal control in the food supply chain

Abstract: Fungi that spoil foods or infect crops can have major socioeconomic impacts, posing threats to food security. The strategies needed to manage these fungi are evolving, given the growing incidence of fungicide resistance, tightening regulations of chemicals use and market trends imposing new food-preservation challenges. For example, alternative methods for crop protection such as RNA-based fungicides, biocontrol, or stimulation of natural plant defences may lessen concerns like environmental toxicity of chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 117 publications
0
34
0
1
Order By: Relevance
“…Fungi are an integral part of the natural environment, and although they have many positive roles, such as for industrial exploitation in the pharmaceutical, cosmetic, agricultural and food industries [ 1 , 2 , 3 , 4 , 5 ], they are also major contributors to food spoilage. Pathogenic fungi are responsible for up to a 20% loss of global crop yields yearly, which includes the loss of 125 million tons of the five most cultivated food crops, while 10% of crops are destroyed during post-harvest [ 6 ]. Fungicides and fungistatics are therefore widely used chemicals that are typically of synthetic origin, and these kill parasitic fungi or their spores, or inhibit their growth, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi are an integral part of the natural environment, and although they have many positive roles, such as for industrial exploitation in the pharmaceutical, cosmetic, agricultural and food industries [ 1 , 2 , 3 , 4 , 5 ], they are also major contributors to food spoilage. Pathogenic fungi are responsible for up to a 20% loss of global crop yields yearly, which includes the loss of 125 million tons of the five most cultivated food crops, while 10% of crops are destroyed during post-harvest [ 6 ]. Fungicides and fungistatics are therefore widely used chemicals that are typically of synthetic origin, and these kill parasitic fungi or their spores, or inhibit their growth, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural and eco-friendly methodologies for food preservation have been proposed in the last few years, but only limited data are available about the usefulness of most of them under industrial scale conditions, which needs proper attention to satisfy the requirements of the industry as well as the demand of the consumers [226][227][228][229][230]. Consequently, studies about the ability of the reported biopreservative agents to control the development of undesirable microorganisms when applied at the industrial scale are greatly required.…”
Section: Discussionmentioning
confidence: 99%
“…Under the current conditions of the intensive agriculture, crop cultivation strongly requires efficient disease control systems to prevent significant crop losses [1][2][3]. Among the most dangerous plant pathogens, pathogenic fungi take one of the leading positions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of its biological and economical expediency, a wide use of various chemical fungicides resulted in the drop of their efficiency [9], as well as a significant accumulation of fungicide residues in the soil, water and agricultural production, which poses a serious threat for humans, animals and the whole ecosystem [10,11]. Moreover, a progressing resistance of plant pathogens to the chemicals used was revealed [2,3,12,13].…”
Section: Introductionmentioning
confidence: 99%